▼Febuxostat for gout. Issue 7 (14th July 2010) - Unknown
Abstract : Around 1.4% of the UK population have gout, the prevalence of which increases with age to around 3% in women and 7% in men aged over 75 years.1 – 3 Acute gout is intensely painful and can reduce patients' quality of life.2, 3 It occurs when the serum uric acid concentration (SUA) rises (hyperuricaemia) and persists above the solubility threshold of monosodium urate (400μmol/L [6.8mg/dL]), leading to urate crystal formation that causes arthritis, gouty tophi (nodules) in subcutaneous tissues and renal calculi.3 – 5 The mainstay of treatment for chronic gout is allopurinol, which inhibits xanthine oxidase (an enzyme involved in the production of uric acid in the body). However, this drug has to be stopped in a minority of patients due to rashes or hypersensitivity.6 ▼Febuxostat (Adenuric – Menarini/Ipsen), another xanthine oxidase inhibitor, is a newly licensed treatment for chronic hyperuricaemia in conditions where urate deposition has occurred.7 Here we consider its place for patients with gout.